Pengembangan Media Pembelajaran Economic Monopoly Board (ECOMO) Pada Pembelajaran IPS Materi Kegiatan Ekonomi di Sekolah Dasar - Sundari, Amala; Yuniarti, Yeni; Arifin , Muh. Husen (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
To achieve learning objectives, teachers must choose the right learning media to teach students the material. This study aims to determine the development of learning media, find out the results of feasibility tests, teacher and student responses, and find out the learning outcomes of students to the application of Economic Monopoly Board (ECOMO) learning media in social studies learning material for grade IV economic activities in elementary schools. The method used in this study uses the design and development method with the ADDIE research model uses qualitative and quantitative data analysis techniques. Participants in this study were material expert validators, media experts and linguists, and involved 24 students and 1 grade IV teacher at elementary school 4 Cipaku. Based on the results of material expert validation, a score of 87.5%, media experts of 97.14%, linguists of 98%, teacher response questionnaires of 98%, student response questionnaires of 93.8% with the category of "very feasible". Student learning outcomes are calculated using the N-Gain score formula, a result of 0.856 with a high category and interpreted in the form of a score of 85.6% with an effective classification. Then, the Learning Media ECOMO in social studies learning material for grade IV economic activities in elementary schools is good, feasible, and effectively used in learning activities.